Time for a culture change: understanding and reducing risk, morbidity and mortality from COVID-19 in those of black and minority ethnicity. (2nd May 2020) - Singh, Iqbal; Chand, Kailash; Singh, Arun; Kandadi, Kondal R
Abstract : Following a number of epidemics in the 21st century, including Ebola and Middle East respiratory syndrome, the SARS-COV-2 virus, causing COVID-19 disease, was declared a pandemic health emergency of international concern in January 2020.